Analysis of Zero Waste Behaviors in Poland - Iwona ZDONEK (Communications of International Proceedings, 2021)
Zero Waste is the approach to waste management that prioritizes waste reduction and material recovery. The purpose of the article is to investigate if the Z generation shows Zero Waste behaviors. The research was carried out concerning the 5R principles. In particular, it was investigated: 1) How common are 5R behaviors in Z generation? 2) What is the acceptance of products and packaging in line with the Zero Waste concept? 3) Does gender determine 5R behaviors? The research was of a pilot nature and was conducted using an online questionnaire. Data visualization on box plots, measures of descriptive statistics, and non-parametric independent-sample comparison tests were used for data analysis. The results of the research indicate that in Poland behaviors towards refusing and reduction are not common. In turn, the reuse, recycle, and rot behaviors are frequent. Furthermore, the research revealed that the acceptance rate of products and packaging in line with the Zero Waste concept is very high. Most of the behavior consistent with the concept is more characteristic of women. On the other hand, the place of living determines whether there are behaviors towards composting bio-waste.
Keywords: Zero Waste Behaviors; 5R Behaviors; Ecological Behaviors; Plastic Management; Food Management.